Electron–phonon superconductivity in C-doped topological nodal-line semimetal Zr5Pt3: a muon spin rotation and relaxation (μSR) study. (2nd November 2021) - Bhattacharyya, A; Ferreira, P P; Panda, K; Masunaga, S H; de Faria, L R; Correa, L E; Santos, F B; Adroja, D T; Yokoyama, K; Dorini, T T; Jardim, R F; Eleno, L T F; et al.
Abstract: In the present work, we demonstrate that C-doped Zr5 Pt3 is an electron–phonon superconductor (with critical temperature T C = 3.8 K) with a nonsymmorphic topological Dirac nodal-line semimetal state, which we report here for the first time. The superconducting properties of Zr5 Pt3 C0.5 have been investigated by means of magnetization, resistivity, specific heat, and muon spin rotation and relaxation (μSR) measurements. We find that at low temperatures, the depolarization rate is almost constant and it can be well described by a single-band s ‐wave model with a superconducting gap of 2Δ(0)/ k B T C = 3.84, somewhat higher than the value of BCS theory. From the transverse field μSR analysis, we estimate the London penetration depth λ L = 469 nm, superconducting carrier density n s = 1.83 × 10 26  m −3, and effective mass m * = 1.428 m e . The zero field μSR confirms the absence of any spontaneous magnetic field in the superconducting ground state. In order to gain additional insights into the electronic ground state of C-doped Zr5 Pt3, we also performed first-principles calculations within the framework of density functional theory (DFT). The observed homogenous electronic character of the Fermi surface as well as the mutual decrease of T C and density of states at the Fermi level are consistent with the experimental findings of this study. However, the band structure reveals the presence of robust, gapless fourfold-degenerate nodal lines protected by 63 screw rotations and glide mirror planes. Therefore, Zr5 Pt3 represents a novel, unprecedented condensed matter system to investigate the intricate interplay between superconductivity and topology.